Development of a behaviour‐based measurement tool with defined intervention level for assessing acute pain in cats. (December 2014) - Calvo, G.; Holden, E.; Reid, J.; Scott, E. M.; Firth, A.; Bell, A.; Robertson, S.; Nolan, A. M.
<x xml:space="preserve">Abstract</x> OBJECTIVES To develop a composite measure pain scale tool to assess acute pain in cats and derive an intervention score. METHODS To develop the prototype composite measure pain scale‐feline, words describing painful cats were collected, grouped into behavioural categories and ranked. To assess prototype validity two observers independently assigned composite measure pain scale‐feline and numerical rating scale scores to 25 hospitalised cats before and after analgesic treatment. Following interim analysis the prototype was revised (revised composite measure pain scale‐feline). To determine intervention score, two observers independently assigned revised composite measure pain scale‐feline and numerical rating scale scores to 116 cats. A further observer, a veterinarian, stated whether analgesia was necessary. RESULTS Mean ± sd decrease in revised composite measure pain scale‐feline and numerical rating scale scores following analgesia were 2 · 4 ± 2 · 87 and 1 · 9 ± 2 · 34, respectively (95% confidence interval for mean change in revised composite measure pain scale‐feline between 1 · 21 and 3 · 6). Changes in revised composite measure pain scale‐feline and numerical rating scale were significantly correlated (r = 0 · 8) (P < 0001). Intervention level score of ≥4/16 was derived for revised composite measure pain scale‐feline (26 · 7% misclassification) and ≥3/10 for numerical rating scale (14 · 5% misclassification). CLINICAL SIGNIFICANCE A valid instrument with a recommended analgesic intervention level has been developed to assess acute clinical pain in cats that should be readily applicable in practice.